Coastal indices to assess sea-level rise impacts - A brief review of the last decade. (15th April 2023) - Rocha, Carolina; Antunes, Carlos; Catita, Cristina
Abstract: The present review intends to serve as the most comprehensive work of the current scientific and the most updated research on coastal vulnerability and risk assessment due to sea-level rise. The article describes the existing scientific knowledge on an important subject that must be in the present climate change agenda, giving examples of methods, methodologies and applications that have been made around the world that can be considered for application according to the specifics of each geographical area. This research demonstrates, with 37 studies of the last decade, that a wide range of concepts, methods, parameters and indices have been used in this context, considering different types of time and space scales for the operation of coastal processes, categorizing them in different intervals and classifying each variable results in a large spectrum of vulnerability and risk levels. In light of the research included in this study, Coastal Vulnerability Index (CVI) is the most popular designation of the index (78%). It was discovered that the index designation provided by the authors is erroneous in 31 studies. Only 7 of the 29 studies that were designated as CVI were genuinely CVI. Coastal forcing factors were employed in 24 studies, however, only half (18 studies) included socioeconomic parameters and only 7 used economic damage parameters. This demonstrated that there is no magic or right formula for assessing vulnerability and risk, as this is largely conditioned by the availability of data and the place it is applied. However, the lack of harmonization in the nomenclature of the indices is worrying. This article also guides how the different indices should be designated, considering what they represent, and what kind of parameters are being used, taking into account the scale on which the study is being applied. Graphical abstract: Image 1 Highlights: Index-based methods are the most common for sea-level rise risk assessment. The lack of harmonization in the nomenclature of the indices is worrying. Most studies only use physical and/or sociodemographic factors in risk assessment. The omission of economic factors limits the risk assessment of vulnerable areas. Coastal economic damage is usually calculated independently.